ANALISIS STRATEGI MANAJEMEN KEPEMIMPINAN KEPALA SEKOLAH GUNA MENINGKATKAN KINERJA GURU PADA PONDOK PESANTREN ASH-SHIDIQIYAH - Bastomi Bastomi; Ahmad Sibron; Yuniar Yuniar; Indah Wigati (Raudhah - Proud To Be Professional, 2023)
School principals must have a good leadership management strategy to improve teacher performance. This research aims to explain and describe the Principal's Leadership management strategy in helping teachers to improve the quality of their performance at the Ash-Shidiqiyah Islamic Boarding School. This type of research is descriptive research with a qualitative approach. Data collection techniques in this research consist of observation, interviews and documentation. The research results show, to improve the quality of teacher performance in educating students, school principals also have good management strategies by providing role models to teachers by attending school on time, optimizing disciplinary regulations in attendance. Apart from that, the Principal tries to work collaboratively with teachers by appointing teachers who he considers capable to carry out supervision. The principal also coordinates with the picket officers who each day consist of 2 officers, namely teachers who do not have teaching hours that day and one person from administration. The picket officer will circulate a list of teacher attendance in the class that has been created so that you can see the level of teacher attendance in each class.